Estimating phosphate capacities of multi-component slags by mass triangle model - Wang, Lijun; Hou, Pengtao; Wang, Yaxian; Chou, Kuochih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Considering the importance of dephosphorization process in ironmaking and steelmaking, this paper attempted to estimate the phosphate capacities of different systems. Mass triangle model could approach the properties of multi-component systems without the parameter for every component. This present work also extended the mass triangle model to multi-component systemsApplication to three systems containing as much as seven components proved the feasibility and accuracy of this model. The calculated contour lines revealed the reasonable trend as experimental results, and calculation results for fixed compositions showed a low error rate. Scattered points calculation obtained more accurate results. Since this model can also evaluate other properties of slag, such as density, viscosity, sulphidecapcity etc., this model might shoot light on theunderstanding of various properties of multi-component slags accurately, and thus offer insight on optimization of ironmaking and steelmaking process.